Development review and prospects of intelligent technology in rail transit vehicles - LONG Teng; WANG Yuyi; LIN Jun; SHI Ke; PAN Wenbo; KANG Gaoqiang (机车电传动)
With the continuous development of technologies such as perception, decision, control, and diagnosis towards intelligence, the integration of intelligent features into vehicular applications has emerged as a prominent trend in the future development of rail transportation. This paper provides a comprehensive overview of the current status and future expectations of key onboard technologies, including automatic train operation (ATO), active collision prevention, infrastructure detection, and driver behavior monitoring. These technologies have significantly enhanced the operational efficiency and safety of rail transportation, along with profound potential for further advancements. Specifically, the train automatic operation technology aims to achieve more accurate and efficient operation of trains, thereby significantly reducing the risks associated with human operational errors. The active collision prevention technology enables automated avoidance between trains, such effectively precluding collision accidents. Furthermore, the infrastructure detection and driver behavior monitoring technology facilitates timely warnings in cases of equipment failure or driver fatigue, ultimately reducing potential hazards. With the further application of these technologies, rail transit vehicles will witness further innovation and development based intelligence, providing robust support for efficient, safe, and intelligent operation of rail transportation in the future.